2014
DOI: 10.1101/gad.240291.114
|View full text |Cite
|
Sign up to set email alerts
|

Tension-dependent removal of pericentromeric shugoshin is an indicator of sister chromosome biorientation

Abstract: During mitosis and meiosis, sister chromatid cohesion resists the pulling forces of microtubules, enabling the generation of tension at kinetochores upon chromosome biorientation. How tension is read to signal the bioriented state remains unclear. Shugoshins form a pericentromeric platform that integrates multiple functions to ensure proper chromosome biorientation. Here we show that budding yeast shugoshin Sgo1 dissociates from the pericentromere reversibly in response to tension. The antagonistic activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 107 publications
7
110
0
Order By: Relevance
“…It is possible that Shugoshin proteins participate in the detection and/or correction of attachment error. Consistently, evidence has been presented for the biorientation-dependent removal of Shugoshin from pericentromeres (Eshleman and Morgan 2014;Nerusheva et al 2014), suggesting that retaining this protein at centromeres and pericentromeres may be a crucial element that keeps the spindle assembly checkpoint at an "on" state before the establishment of biorientation. However, how Shugoshin interacts with SAC remains an open question.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…It is possible that Shugoshin proteins participate in the detection and/or correction of attachment error. Consistently, evidence has been presented for the biorientation-dependent removal of Shugoshin from pericentromeres (Eshleman and Morgan 2014;Nerusheva et al 2014), suggesting that retaining this protein at centromeres and pericentromeres may be a crucial element that keeps the spindle assembly checkpoint at an "on" state before the establishment of biorientation. However, how Shugoshin interacts with SAC remains an open question.…”
supporting
confidence: 69%
“…Sgo1p undergoes biorientation-dependent removal from chromatin (Nerusheva et al 2014), suggesting that Sgo1p and, in particular, its interaction with chromatin is tightly linked to the status of tension. Pericentric chromatin structural changes seem to be an obligatory outcome of bipolar attachment (Haase et al 2012;Verdaasdonk et al 2012;Stephens et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that Ipl1 kinase and Sgo1 are required to prevent SAC silencing in response to syntelic attachment induced by CIK1-CC overexpression (Jin et al 2012;Jin and Wang 2013). Because the centromere localization of Sgo1 depends on H2A phosphorylation by Bub1 kinase (Fernius and Hardwick 2007;Kawashima et al 2010;Nerusheva et al 2014), Bub1 kinase activity might be required to prevent SAC silencing in response to syntelic attachment, although this kinase activity is dispensable for SAC activation (Fernius and Hardwick 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of budding yeast H2A at serine 121 by Bub1 is essential for centromere localization of Sgo1, and phospho-deficient h2a-S121A mutant fails to recruit Sgo1 to centromeres (Kawashima et al 2010;Nerusheva et al 2014). Thus, we postulated that h2a-S121A mutants would show premature SAC silencing similar to bub1-DK and sgo1D mutants.…”
Section: The Phosphorylation Of H2a By Bub1 Prevents Sac Silencingmentioning
confidence: 99%
“…PP2A Cdc55 contributes to progression through the G2/M checkpoint and prevents early mitotic exit (Queralt et al 2006;Wang and Ng 2006;Yellman and Burke 2006;Rossio and Yoshida 2011). PP2A Rts1 localizes to centromeric chromatin, where it promotes condensin loading and functions in the tension-sensing mechanism of the spindle assembly checkpoint (Chan and Amon 2009;Nerusheva et al 2014;Peplowska et al 2014;Verzijlbergen et al 2014). Further, PP2A Rts1 coordinately regulates cell cycle entry and the cell size checkpoint, in part by relieving transcriptional repression of the G1 cyclin Cln3, but the mechanism of this control is not yet fully defined (Artiles et al 2009;Zapata et al 2014).…”
mentioning
confidence: 99%